Tratamiento de efluentes de la industria minera con dolomita - Romero Baylón, Alfonso (2010)
The article shows a methodology for acid water treatment, through the remediation of effluents from the mining industry, based on the use of treated dolomite, which reduces the concentrations of dissolved heavy metal ions in metallurgical and mining effluent to reducing high levels of heavy metals, which are indicators of improved water quality of industrial wastes, mainly from metallurgical processes concentrator plants. This treatment technique solves the problem of effluent generation with the use of dolomite, which is a nonmetallic mineral double calcium carbonate and magnesium (CaCO3.MgCO3), which acts as an effective reagent for remediation, because its physicochemical properties of the acid neutralizing acid water and adsorption of dissolved metal ions in acidic waters. Moreover, the implementation of this remediation treatment, proposes to establish a working methodology to develop a cleaning technology at the laboratory, with prospects to develop clean technology to pilot plant level, with subsequent development of a treatment plant remediation at the industrial level.